Chiropractic spinal manipulative therapy for migraine: a study protocol of a single-blinded placebo-controlled randomised clinical trial. Issue 11 (19th November 2015) - Chaibi, Aleksander; Šaltytė Benth, Jūratė; Tuchin, Peter J; Russell, Michael Bjørn
Abstract : Introduction: Migraine affects 15% of the population, and has substantial health and socioeconomic costs. Pharmacological management is first-line treatment. However, acute and/or prophylactic medicine might not be tolerated due to side effects or contraindications. Thus, we aim to assess the efficacy of chiropractic spinal manipulative therapy (CSMT) for migraineurs in a single-blinded placebo-controlled randomised clinical trial (RCT). Method and analysis: According to the power calculations, 90 participants are needed in the RCT. Participants will be randomised into one of three groups: CSMT, placebo (sham manipulation) and control (usual non-manual management). The RCT consists of three stages: 1 month run-in, 3 months intervention and follow-up analyses at the end of the intervention and 3, 6 and 12 months. The primary end point is migraine frequency, while migraine duration, migraine intensity, headache index (frequency x duration x intensity) and medicine consumption are secondary end points. Primary analysis will assess a change in migraine frequency from baseline to the end of the intervention and follow-up, where the groups CSMT and placebo and CSMT and control will be compared. Owing to two group comparisons, p values below 0.025 will be considered statistically significant. For all secondary end points and analyses, a p value below 0.05 will be used. The results will be presented with the corresponding p values and 95% CIs. Ethics and dissemination: The RCT will follow the clinical trial guidelines from the International Headache Society. The Norwegian Regional Committee for Medical Research Ethics and the Norwegian Social Science Data Services have approved the project. Procedure will be conducted according to the declaration of Helsinki. The results will be published at scientific meetings and in peer-reviewed journals. Trial registration number: NCT01741714.